Study on Instability Mechanism and Support Scheme of the Tunnel Face in Carbonaceous Phyllite Stratum under High Geo-Stress. (23rd August 2022) - Pu, Song; Yu, Tao; Ye, Laibin; Liao, Hang; Fang, Yong; Yao, Zhigang; Wang, Jun
Abstract : The tunnel face collapses easily during tunnel construction in weak surrounding rock under high geo-stress. Identifying the instability mechanism of the face and proposing targeted control measures are of great importance to prevent the collapse of the face. Using the setting of the carbonaceous phyllite stratum of the Baima tunnel, a FLAC 3D -PFC 3D coupled model is used to analyze the influential factors on the stability of the face and optimize the original support scheme. The results show that the instability of the face is rooted in the collapse of the rock above the face, and the bench method with short cycle footage is more conducive to the stability of the face. Compared with single support mode of advanced small pipes, the combined support scheme of long bolts and small pipes can better control the displacement of the surrounding rock and prevent the collapse of the tunnel face. The numerical simulation and field surrounding rock monitoring results verify the rationality of the excavation method, the cycle footage, and the support system. This finding will be of great significance to guide design and construction in weak surrounding rock.